A New In Vivo Model System to Assess the Toxicity of Semiconductor Nanocrystals - Angela Tino; Alfredo Ambrosone; Lucia Mattera; Valentina Marchesano; Andrei Susha; Andrey Rogach; Claudia Tortiglione (International Journal of Biomaterials)
In the emerging area of nanotechnology, a key issue is related to the potential impacts of the novel nanomaterials on the environment and human health, so that this technology can be used with minimal risk. Specifically designed to combine on a single structure multipurpose tags and properties, smart nanomaterials need a comprehensive characterization of both chemicophysical properties and adequate toxicological evaluation, which is a challenging endeavour; the in vitro toxicity assays that are often employed for nanotoxicity assessments do not accurately predict in vivo response. To overcome these limitations and to evaluate toxicity characteristics of cadmium telluride quantum dots in relation to surface coatings, we have employed the freshwater polyp Hydra vulgaris as a model system. We assessed in vivo acute and sublethal toxicity by scoring for alteration of morphological traits, population growth rates, and influence on the regenerative capabilities providing new investigation clues for nanotoxicology purposes.